A Brief History of Wires in the Brain - Cobb, Matthew (Frontiers in Ecology and Evolution, 2021)
Metaphors have formed a significant part of the development of neuroscience, often linked with technology. A metaphor that has been widely used for the past two centuries is that of the nervous system being like wires, either as a telegraph system or telephone exchange, or, more recently, in the more abstract metaphor of a wiring diagram. The entry of these terms into scientific writing is traced, together with the insights provided by these metaphors, in particular in relation to recent developments in the study of connectomes. Finally, the place of the wiring diagram as a modern version of Leibniz’s “mill” argument is described, as a way of exploring the limits of what insight the metaphor can provide